Multipli keratoakantomi - Vidmar, Vesna (Medicinski razgledi, 2011)
Keratoacanthoma is an epidermal malignancy, which histopathologically resembles to squamous cell carcinoma. Multiple keratoacanthomas are a heterogenous group of inherited or acquired disorders. Several different mechanisms may be responsible for their development, including UV radiation, ionizing radiation, viruses (human papillomavirus), and chemical carcinogens (tar), as well as certain immunologic and genetic factors. The article is a report on three patients who developed multiple keratoacanthomas and several squamous cell or basal cell carcinomas while receiving photochemotherapy. They had a history of psoriasis of over 40 years' duration and had been periodically treated with systemic photochemotherapy because of generalized psoriasis that was resistant to topical treatment. Throughout the years of treatment with photochemotherapy, they received high cumulative doses of UVA rays. Because of development of these cutaneous tumors, photochemotherapy was discontinued, but continued development of the above-mentioned lesions was nevertheless noticed. Due to frequent recurrences of psoriasis, these patients receive high doses of UVA rays in their lifetime and therefore have a significantly increased risk for the development of nonmelanoma skin malignancies. The occurrence of multiple keratoacanthomas in the presented cases can be attributed with a great probability to long-term photochemotherapy.
Keywords: Keratoacanthoma; Keratoakantom; Koža, novotvorbe; Skin Neoplasms; Psoriasis; Luskavica; Fotokemoterapija; Photochemotherapy; Stranski učinki; adverse effects; kožne bolezni; multipli keratoakantomi; therapy; zdravljenje